Virtual synthesis of nanosystems by design : from first principles to applications - Pozhar, Liudmila A. (Elsevier insights., 2015)
This is the only book on a novel fundamental method that uses quantum many body theoretical approach to synthesis of nanomaterials by design. This approach allows the first-principle prediction of transport properties of strongly spatially non-uniform systems, such as small QDs and molecules, where currently used DFT-based methods either fail, or have to use empirical parameters. The book discusses modified algorithms that allow mimicking experimental synthesis of novel nanomaterials--to compare the results with the theoretical predictions--and provides already developed electronic templates.